Antegrade Therapy for Management of Choledocholithiasis through Endoscopic Ultrasound-Guided Hepaticogastrostomy in a Patient with Surgically Altered Gastrointestinal Anatomy. (12th November 2020) - Dorrell, Robert; Madigan, Katelyn; Pawa, Swati; Pawa, Rishi
Abstract : Endoscopic ultrasound-guided hepaticogastrostomy (EUS-HG) is a technique used to access the biliary tree in patients with surgically altered anatomy. Additionally, development of EUS-HG fistula permits intraductal therapy, thereby preventing patients from requiring surgery or percutaneous transhepatic biliary drainage (PTBD), thus decreasing morbidity. This clinical vignette describes an 83-year-old man with a history of gangrenous cholecystitis requiring cholecystectomy, partial gastrectomy, and Roux-en-Y gastrojejunostomy who presented to an outside hospital with abdominal pain and fever and found to have cholangitis and choledocholithiasis. He underwent two endoscopic retrograde cholangiopancreatography (ERCP) procedures at an outside hospital which were unsuccessful due to an inaccessible major papilla in the setting of the patient's surgically altered anatomy. On arrival to Wake Forest, the patient underwent EUS-HG with successful biliary drainage and resolution of cholangitis. He returned for ERCP three months later with balloon sphincteroplasty, cholangioscopy, and electrohydraulic lithotripsy (EHL) performed through the existing metal stent (hepaticogastrostomy), resulting in stone fragmentation and antegrade removal with balloon sweeps. Repeat cholangioscopy post-EHL and balloon sweeps showed complete duct clearance with no residual stones. The hepaticogastrostomy stent was subsequently removed, and the patient recovered without any complications.